2016
DOI: 10.1177/0194599816644908
|View full text |Cite
|
Sign up to set email alerts
|

ß‐Tricalcium Phosphate Implants in the Surgical Treatment of Empty Nose Syndrome

Abstract: The objective of this study was to assess the efficacy and morbidity of a β-tricalcium phosphate implant in the treatment of empty nose syndrome after turbinectomy. Only patients with a history of inferior turbinectomy and a complaint of permanent paradoxical nasal obstruction were included. β-Tricalcium phosphate ceramic implants were implanted under the mucoperiosteal plane of the lateral nasal wall to replace the head of the inferior turbinate. Symptoms and quality of life were assessed by 2 questionnaires:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…It may be argued that patients suffering from empty nose syndrome (ENS) no longer perceive 1 or several of these types of information, thereby having an impression of nasal obstruction. On the other hand, rebuilding the head of the inferior turbinate seems to improve the symptoms and quality of life of patients suffering from ENS …”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that patients suffering from empty nose syndrome (ENS) no longer perceive 1 or several of these types of information, thereby having an impression of nasal obstruction. On the other hand, rebuilding the head of the inferior turbinate seems to improve the symptoms and quality of life of patients suffering from ENS …”
Section: Discussionmentioning
confidence: 99%
“…Functional outcomes estimated with the SNOT-25 score, showed significant improvement after a 12-week follow-up, SNOT-25 decreased from 77 to 55. Bastier et al (18) reported similar results: they used a b-tricalcium phosphate implant in 14 patients. Quality-of-life (frequency, bothersomeness, impact) significantly improved after surgery.…”
mentioning
confidence: 75%
“…Numerous different nonresorbable filler materials and implants have been previously used in both these entities: autologous costal/septal/ conchal cartilage, 14,15 acellular dermis graft, 2 plastipore plates, 16 and ß-tricalcium phosphate, 17 goretex, or teflon implants. Cartilage graft has the advantage of being an autologous material, with excellent tolerance and integration, but implies a new mucosal trauma by removing septal cartilage and adds donor-site morbidity with costal or conchal grafts.…”
Section: Discussionmentioning
confidence: 99%